Pertumbuhan Ekonomi Kota Batu sebagai Daerah Otonom Baru - Zaenurullah, Lutfi; B, Boedijono; Suryawati, Dina (e-Sospol, 2015)
Abstract Decentralization and local autonomy provide opportunities for the regions (province and regency/city) in Indonesia to undertake regional expansion. The implication is that the number of new autonomous regions (DOB) is higher and higher. However, the DOBs, viewed from the economic growth, tend to be under the parent regions. This means that the DOBs cannot respond to the demands of the expansion goals related to the acceleration of the regional economic development. Batu City was designated as a DOB through Law No. 11 Year 2001 on the establishment of Batu City. The economic growth of Batu City in 2002-2011 continuously increased and was higher than the average growth of Malang Regency which is the parent area of Batu City. This research was intended to determine the role of Batu City Government in improving its economic growth and analyze whether there was a sector shift in Gross Domestic Product (GDP) of Batu City. This type of research is descriptive with qualitative approach. In addition, to identify changes in leading sector of GDP in Batu City used Klassen’s typology analysis.